Complexity Theory 101 for Educators: A fictional account of a graduate seminar - McMurtry, Angus (McGill Journal of Education / Revue des sciences de l'éducation de McGill)

(untitled) (Faculty of Education, McGill University, 2008)
AbstractThe following fictional account of a seminar on complexity science and its relevance for education makes use of several real events. The first is an actual seminar that took place during the spring of 2005, in the Department of Secondary Education at the University of Alberta. The second is the collective creation of the Complexity and Education Online Glossary (McMurtry et al., 2004; see http://www.complexityandeducation.ualberta.ca). Furthermore, many of the ideas presented in this article are based on the definitions originally developed for that glossary.